O PROFESSOR EM FORMAÇÃO INICIAL FRENTE AOS NOVOS CONTEXTOS DE ENSINO MARCADOS PELA IMPLANTAÇÃO DA BNCC E A PANDEMIA DO COVID-19 - Freitas, Karoline da Silva Guedes de (2022)
The present study aims to reflect on the initial training of teachers in the face of so many changes in society, among them, the implementation of the BNCC and the reflexes that the covid-19 pandemic brought to society, more specifically to education, demanding a change from it. of methodologies. In order to develop the research, its general objective was to understand the necessary knowledge for the teacher in the face of the changing educational scenario and how to develop it in the initial training of teachers. In addition, as specific objectives, we sought to produce reflections on the new teaching contexts, in this contemporary society, to understand the new role of the teacher and education; to analyze the initial training of teachers as well as their challenges and possibilities, as well as to think about how initial training contributes to the training of an innovative teacher and to analyze the use of digital technologies in education as a way to improve the teaching and learning process. To achieve these objectives, an exploratory bibliographic study of the theme was carried out, using books and articles that deal with this issue and help to build a reflection on the theme. The research is of a qualitative nature and in this model what matters is the quality of the information, the descriptions and not the numbers, the statistics. It is divided into three chapters, one chapter corresponding to an objective, in the order in which the objectives were placed, that is, each chapter seeks to achieve a specific objective. In the end, it was possible to perceive that digital technologies are present in our daily lives, much more now than before and that is why we also need to use them in favor of education, as the pandemic has shown us to be possible in recent years. For this reason, it is important that initial training courses are also based on technology, in addition to being prepared to form this new professional profile that education needs and seeks.